Dynamics of Child Marriage in Suku Anak Dalam Community - Rahmi Hidayati; Illy Yanti; Muhammad Farhan HR; Shahrul Hilmi Othman (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
This paper aims to explain the dynamics of child marriage and its impact on the Suku Anak Dalam community. This research uses observation, interview, and documentation methods, in which researchers directly go to the field to observe and interview perpetrators of early marriages and tribal chiefs. The results of the study show that the Suku Anak Dalam community has its own rules and traditions regarding the appropriate age limit for marriage and does not include provisions in the law that have been positive. This tradition is a way of measuring the maturity of the bride and groom. According to the Suku Anak Dalam, men can get married if they can earn a living through skill tests in hunting animals or are suitable for farming. At the same time, women are considered adults if they have menstruated. Child marriage is generally a tradition passed down from generation to generation and is an unwritten legal system in society. This practice is a form of neglect regarding women's rights in domestic life, which impacts divorce, physical health, malnutrition, and marriage administration. Several factors, including tradition, arranged marriages/endogamous marriages, economics, promiscuity, and gender inequality, cause this child marriage.